(untitled) - Vaculik, Juraj; Kocianova, Lenka (Doprava a spoje, 2011)
The paper deals with electrical properties of identifiers in RFID technologies and their impact on the operational use in the postal process. It describes the basic parameters and results of their testing in laboratory conditions in terms of properties of antennas, their location, operational settings, distance and the other. There is, In conclusion, the assessment of their applicability to process postal operator.